THE ROLE OF LEARNING METHODS IN INCREASING STUDENTS CREATIVITY IN CLASS 2 AT SDN JRUEK ACEH BESAR - Mughni ‘Alya; Siti Mayang Sari; Fitria Manurung; Sariakin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Education has a crucial role in forming character and improving students abilities. The modern era of education demands the use of learning methods that are not only effective but also responsive to the dynamics of development in society and the world today. Learning methods, in this context, include various strategies, approaches and techniques used by educators to convey lesson material to students. In choosing and implementing learning methods, it is necessary to understand that each student has a different learning style, and an effective learning environment must be able to accommodate this diversity. The aim of this research is to describe the role of learning methods in increasing the creativity of students in grade 2 at SDN Jruek Aceh Besar. This research uses a qualitative approach with descriptive research type. Based on the results of research conducted at SDN Jruek Aceh Besar, the application of a projectbased approach, cooperative learning, and creative experimental methods forms a learning environment that increases student collaboration and creativity. The teacher ensures the suitability of the method to the development of creativity through monitoring, evaluating student responses, and parental involvement. The challenges of integrating creative methods were overcome with school support for teachers, improved facilities, and a collaborative learning community. The teacher's role as a creative facilitator includes creating a supportive and motivating environment.